Laparoscopic Excision of Gastric Mass Yields Intra-abdominal Esophageal Duplication Cyst - Bhamidipati, Castigliano; Smeds, Matthew; Dexter, Elisabeth; Kowalski, Margaret; Bazaz, Sapna (The Thoracic and Cardiovascular Surgeon, 2013)
A 69-year-old man with presumed solid gastric mass determined by computed tomography, endoscopic ultrasonography, and fine-needle aspiration underwent videoscopic excision of what resulted in a cystic structure consistent with intra-abdominal esophageal duplication cyst. Esophageal duplication cysts are rare congenital lesions that are difficult to diagnose. They seldom occur entirely below the diaphragm, and occurrence in adults is unusual. Only six such cases are reported in the literature. When diagnosis is made, treatment decisions are not always straight forward, although excision is frequently pursued. The current case describes this unique finding and presents laparoscopic excision as a safe treatment alternative.
Keywords: duplication cyst; esophagus; videoscopy